THE LEGAL NATURE OF E-COMMERCE IN THE REPUBLIC OF UZBEKISTAN - Muqumov, Bobur (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In modern realities, the vast majority of consumers prefer to receive and pay for goods, works and/or services without leaving home. Commercial banks and other organizations actively provide assistance, creating convenience for the public, in the development, development and application of electronic payment infrastructure. Digitalization of financial services is designed to reduce costs and improve the efficiency of the system, digitalization allows you to increase the number of people served, even in rural regions, due to greater speed and ease of use of a simple interface. The steady advancement of the economy into the virtual space – its rapid digitalization around the world causes an immediate demand for all market participants to make the necessary modifications to the content of their activities. Of course, commercial banks, which are the building blocks of the material development of society, did not stand aside either.